1999
DOI: 10.1046/j.1420-9101.1999.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variation and the evolutionary history of chromosome races of collared lemmings (Dicrostonyx) in the Eurasian Arctic

Abstract: Collared lemmings (Dicrostonyx) demonstrate extensive chromosome variation along their circumpolar distribution in the high Arctic. To reveal the history of this genus and the origin of chromosome races in the Palearctic, we studied the geographical pattern of mtDNA variation in lemmings from 13 localities by using eight tetranucleotide restriction enzymes. The main split in mtDNA phylogeny is at the Bering Strait and corresponds to the main chromosome division between the Beringian and the Eurasian groups of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 52 publications
4
90
1
Order By: Relevance
“…These lineages demonstrate the extensive genetic diversity of Late Pleistocene populations (Fig. S1), a distinct contrast to the genetically depauperate populations reported for this species at present (11). Ancient DNA studies have consistently reported postglacial loss of genetic diversity in northern Holarctic mammal species (12), including collared lemmings (13).…”
Section: Population History Of Late Pleistocene Collared Lemmingsmentioning
confidence: 71%
“…These lineages demonstrate the extensive genetic diversity of Late Pleistocene populations (Fig. S1), a distinct contrast to the genetically depauperate populations reported for this species at present (11). Ancient DNA studies have consistently reported postglacial loss of genetic diversity in northern Holarctic mammal species (12), including collared lemmings (13).…”
Section: Population History Of Late Pleistocene Collared Lemmingsmentioning
confidence: 71%
“…Further evidence in support of the hypothesis has come from the study of fossil pollen, plant macros including wood charcoal, and mammals (Birks 2003;Willis & van During the last glaciation, many cold-adapted species had a larger distribution than they have today. Furthermore, several studies on cold-adapted species have identified genetic signatures of increase in population size during the early stages of the last glaciation, suggesting that these species had small population sizes also during the last interglacial (Fedorov et al 1999;Flagstad & Røed 2003;Shapiro et al 2004;Dalén et al 2005). It therefore seems likely that glacial expansions and interglacial contractions were a recurrent pattern for cold-adapted species during the Late Quaternary.…”
Section: Spatial and Temporal Categories Of Refugiamentioning
confidence: 99%
“…We have also included snap traps set for genetic analyses in places with indications of lemming activity (Fedorov et al 1999). This resulted in an average of 164 extra trap-nights at each site (range = 48-331, SD = 63).…”
Section: Lemming Samplingmentioning
confidence: 99%